COMBATE À VIOLÊNCIA DOMÉSTICA: Ações de educação popular desenvolvidas pelo Centro de Referência e Atendimento à Mulher - CRAM em Açailândia – MA - RIBEIRO, Léia de Oliveira (2023)
The theme of the dissertation is motivated by my experience as a lawyer at the Center for Reference and Assistance to Women in Açailândia MA - CRAM - a body that welcomes and assists women in conditions of domestic and family violence, as well as my militancy in human rights, and a member of the Commission of Women and Lawyer of the Brazilian Bar Association – OAB MA. The work carried out at CRAM in the fight against violence against women as a warranty of human rights is carried out in two ways: Women who are victims of domestic violence assisted (ansured by the protective measure granted by the Justice), and preventive work through popular education in which it encourages women to identify whether or not they are experiencing an abusive relationship, and how to guide them in the process of reporting. The latter, preventive work through popular education, is the object of this dissertation. For this, it sought to understand the conceptions of the researched women about what they understand as domestic violence, education as a form of social transformation; how they see themselves as women. From this, we build reflections on autonomy, empowerment. In the methodological field, we carried out an action research with the participation of 9 (nine) women, all attended at CRAM. It is a qualitative study. Observations, field diary, document analysis and culture circles were used for data construction. From this, the themes, subthemes, words and generating expressions were organized. In the analysis of the constructed data and in the considerations, we sought to reflect on the situation-problem-challenge. Among other results up to this point in the research (qualification), it appears that the women already understand that they have lived or are in an abusive relationship, and are looking for information, strengthening and knowledge to break the cycle of violence.